2009
DOI: 10.1074/jbc.m109.003202
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Histone H3 at the Nucleosome Dyad Alters DNA-Histone Binding

Abstract: Histone post-translational modifications are essential for regulating and facilitating biological processes such as RNA transcription and DNA repair. Fifteen modifications are located in the DNA-histone dyad interface and include the acetylation of H3-K115 (H3-K115Ac) and H3-K122 (H3-K122Ac), but the functional consequences of these modifications are unknown. We have prepared semisynthetic histone H3 acetylated at Lys-115 and/or Lys-122 by expressed protein ligation and incorporated them into single nucleosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(157 citation statements)
references
References 45 publications
(35 reference statements)
3
153
1
Order By: Relevance
“…This shift could be the result of altered interactions between histone H3 and the cellular machinery or direct effects on histone-DNA interactions. In support of the latter, it has been shown that neutralization of charge in this area by acetylation of H3 K122 destabilizes the nucleosome in vitro (Manohar et al 2009). To test between these two possibilities, we monitored the positioning of recombinant nucleosomes containing yeast H3 and yH3 a3h on DNA in vitro.…”
Section: Resultsmentioning
confidence: 89%
“…This shift could be the result of altered interactions between histone H3 and the cellular machinery or direct effects on histone-DNA interactions. In support of the latter, it has been shown that neutralization of charge in this area by acetylation of H3 K122 destabilizes the nucleosome in vitro (Manohar et al 2009). To test between these two possibilities, we monitored the positioning of recombinant nucleosomes containing yeast H3 and yH3 a3h on DNA in vitro.…”
Section: Resultsmentioning
confidence: 89%
“…In this second set of mutations, we also made acetylation mimics (Lys 3 Gln) at the same lysine residues that were mutated to arginine residues. The Lys 3 Gln substitution is often used to mimic the acetylated form of the Lys residue (62)(63)(64)(65)(66). As shown in Fig.…”
Section: Effects Of Small Molecule Modulators Of Sirt1 On Transcriptimentioning
confidence: 99%
“…For example, in their studies on DNA damage-induced acetylation of lysine 3016 of ataxiatelangiectasia mutated kinase, a modification that activates ataxia-telangiectasia mutated kinase, Sun et al (65) found that glutamine did not substitute for acetyl-lysine in ataxia-telangiectasia mutated kinase. In another example, Manohar et al (66) showed in studies on nucleosome dyad acetylation that the Lys 3 Gln substitution did not fully replicate the role of lysine acetylation; they found that the Lys 3 Gln substitution mimicked the change in charge but was a very poor mimic of the steric effect of acetylation. Thus, our findings may indicate that in addition to deacetylation of wild-type Nrf2, thereby inhibiting its transcriptional activity, SIRT1 expression may also affect Nrf2 activity by an additional mechanism when acetylatable lysines are mutated to glutamine.…”
Section: Effects Of Small Molecule Modulators Of Sirt1 On Transcriptimentioning
confidence: 99%
See 1 more Smart Citation
“…Although these data are highly valuable, a potential pitfall for the mutagenesis approach is that lysine to glutamine and arginine only moderately mimics the lysine in the acetylated and unacetylated form, respectively. 149,150 . Because the K274 in MOF or K327 in Tip60 resides near the head group of AcCoA, a chemical change to this residue may alter the active site microenvironment, thus compromising the catalytic activity of MYST proteins.…”
Section: Discussionmentioning
confidence: 99%